Characterisation of standardised fraction from clinacanthus nutans (SF1) and its anti tumor effects on in vitro and xenograft model - Zainuddin, Nik Aina Syazana Nik (2020)
Cervical cancer is a leading cause of death in women, worldwide, and third in Malaysia. Nowadays, medicinal plants become an alternative treatment due to side effects of conventional treatment and easily available. Clinacanthus nutans has been locally recognized and was claimed for cancer treatment. From our pilot study, a fraction of C. nutans shown a potent inhibition on human cervical cancer cells, in vitro. Therefore, this study was conducted to characterize active anticancer compounds from C. nutans and determine tumor suppression effect with its mechanism in order to evaluate the potential of C. nutans as an alternative treatment for cervical cancer. Initially, optimization methods of bioassay-guided fractionation was carried out. All collected fractions of C. nutans were examined for cytotoxic activity towards human cervical cancer cell lines, HeLa and SiHa, and normal cell line, NIH by MTT Assay. The most potent standardized fraction, SF1 was characterised and identified by Fourier Transform Infrared (FTIR), Liquid Chromatography Mass Spectrometer (LCMS) and quantitative phytochemical analysis. The anticancer mechanism of SF1 was evaluated by flowcytometric analysis for cell cycle progression, mode of cell death and protein expression using Annexin- V/propidium iodide double staining and specific antibody conjugated fluorescent dye; Bax, Bcl-2, p53 and cytochrome C. Further investigation of SF1 on tumor suppression effect was conducted using xenografted nude mice as a model of living subject. The nude mice were subcutaneously inoculated with SiHa cells. Tumor volume and body weight were recorded at 3 days intervals. When tumor volume reached 100 mm3, SF1 was administered once daily via intraperitoneal injection for 28 days. Tumor and liver were surgically removed and fixed for hematoxylin and eosin (H&E) staining and immunohistochemistry (IHC) using caspase-3. Blood was collected by cardiac puncture for assessment of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) level. The findings suggested that the major constituent of SF1 was identified as alkaloid with functional group, amines. SF1 exhibited better cytotoxicity with best growth inhibition against SiHa (IC50 = 9.98±1.24 μg/ml) compared to HeLa (IC50 = 81.21±1.17 μg/ml) and showed cytoselectivity with no IC50 detected on NIH cells. SF1 induced early apoptosis in SiHa cells with arrested cell cycle at G1/S checkpoint. Up-regulation of p53 followed by increasing of pro-apoptotic Bax and decreasing of anti-apoptotic Bcl-2 as well as increment of cytochrome C levels upon treatment with SF1 were also shown. The results showed that tumor volume (60.18±2.17 mm3) in SF1-treated mice were reduced compared to negative control (139.16±12.97 mm3). Upon SF1 treatment, 43.74± 2.27% of relative tumor growth ratio (T/C) and 0.64±0.03 of relative tumor volume (RTV) were calculated. SF1 showed a good inhibition rate with more than 50% of tumor were suppressed. ALT and AST level in SF1-treated mice were remained in normal ranges compared to cisplatin group indicating no sign of toxicity effects. The H&E analysis revealed no abnormal toxicity condition on liver and reduced number of mitosis on tumor upon treatment with SF1. The IHC analysis confirmed an increased expression of a crucial mediators of apoptosis, caspase-3, in SF1-treated mice. In conclusion, SF1 demonstrated anticancer activity by inducing apoptosis through arrested G1/S cell cycle checkpoint via p53 mediated mitochondrial pathway. The tumor suppression effect of SF1 was demonstrated on the growth of xenografted human cervical cancer in nude mice. Thus, these findings provided a data for a potential of SF1 as future therapeutic drug for cervical cancer treatment